A ideia de natureza na obra “Os sofrimentos do jovem Werther” de Goethe - Silva, Nicolas Mateus Ferreira da (2020)
The present work aims to understand and analyze the conception of Nature by the author Johann Wolfgang von Goethe; thus, we will analyze his novel “The Sorrows of Young Werther”. The book is one of the main works of the German philosophical movement Sturm Und Drang, and has a conception of Nature that contrasts with that which the Modern Science established during the sixteenth and eighteenth centuries. Modern Science authors saw the Nature from the perspective of mathematics and fragmentation, mechanized and merely as a resource to be dominated and exploited by Man. On the other hand, Goethe presents in Werther a conception of Nature seen from the perspective of art, understanding it as a living organism that is in unity with Man. This work was structured as follows: in the first chapter we present the general context, the main authors and their contributions to Modern Science regarding the conception of Nature. In the second chapter, we explore the Goethean context and how Nature was seen in the philosophical movements Sturm Und Drang and German Romanticism. Finally, in the third chapter, we seek to present and dialogue with Werther bringing from the book elements which show how Goethe dealt with nature, as well as he sought to oppose the idea settled by the authors of the Modern Science.